The effect of financial governance on performance of Government Ministries in Kenya - Keter, Marystellah Nanjala; Mouni, Dr. Gedion (Journal of Public Policy and Administration, 2017)
Purpose: The purpose of this study is to establish the effect of financial governance on performance contracting results of Government Ministries in Kenya. Methodology: The study used a descriptive research design. The target population of the study is Divisional heads, middle level managers and supervisors in 3 selected government ministries. These were Ministry of Education, Science & Technology, Ministry of Health and Ministry of Environment, Water& Natural Resources. Sample of 55 respondents was used. Results: Result findings showed that financial governance influences performance contracting results of Government Ministries in Kenya positively. Policy recommendation: Based on the finding the study recommends that the government should encourage prudent use of financial resources.